Associations between temperament dimensions and dental anxiety in parents of the FinnBrain Birth Cohort Study - Arkkila Juuso; Suominen Auli; Nolvi Saara; Rantavuori Kari; Karlsson Hasse; Karlsson Linnea; Lahti Satu (WILEY, 2022)
We evaluated associations between dental anxiety and four temperament dimensions: effortful control, extraversion/surgency, negative affect and orienting sensitivity among 2558 parents in the FinnBrain Birth Cohort Study. Dental anxiety was measured with the Modified Dental Anxiety Scale, and temperament with the Adult Temperament Questionnaire. Associations between dental anxiety and temperament dimensions were modelled using linear and logistic (cut-off >= 19 for high dental anxiety) regression analyses adjusting for general anxiety and depressive symptoms, age and education. In women and men, dental anxiety was positively associated with negative affect (women beta = 1.10; 95%CI 1.06-1.15; men beta = 1.11; 95%CI 1.05-1.18) and negatively associated with effortful control (women beta = 0.95; 95% CI0.92-0.99, men beta = 0.90; 95% CI 0.85-0.95). In women, extraversion/surgency was also positively associated with dental anxiety (beta = 1.04; 95%CI 1.00-1.08). For high dental anxiety, negative affect in women (OR = 2.00; 95%CI 1.31-3.06) and men (OR = 5.21; 95%CI 1.72-15.83) and for extraversion/surgency in women (OR = 1.50; 95%CI 1.01-1.47) associated positively with dental anxiety, but for effortful control, the association was not statistically significant. Dentists should understand that temperament dimensions affect the risk for dental anxiety more strongly than general anxiety or depressive symptoms. Dimensions negative affect and extraversion/surgency may increase and effortful control decrease the risk.